Search for pair production of vectorlike quarks in the fully hadronic final state; Physical Review D; Vol. 100, iss. 7 - Sirunyan A. M.; Tumasyan A. R.; Adam W. Wolfgang; Ambrogi F. Federico; Bergauer T. Thomas; Babaev A. A. Anton Anatoljevich; Yuzhakov A. D. Aleksandr Dmitrievich; Okhotnikov V. V. Vitaly Vladimirovich (2019, 2019)
Title screen